Earlier point-of-care ultrasound, shorter length of stay in patients with acute flank pain - Pei-Hsiu Wang (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2022)
Abstract Background The effects of early integration of point-of-care ultrasound (PoCUS) into patient care are uncertain. This study aims to investigate the effects of early PoCUS on patients with acute flank pain. Methods Adult non-traumatic patients with acute flank pain receiving PoCUS were enrolled. Expert physicians reviewed the medical records and made the “final diagnosis” for the cause of acute flank pain. The primary outcome was the relationship between the door to ultrasound (US) time and length of stay (LOS). The secondary outcomes included the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of the sonographic diagnosis, compared with the final diagnosis. Results Eight hundred and eighty-eight patients were included in the analysis. Patients receiving early PoCUS (≤120 min) had a shorter LOS (128 vs. 217 min, p < 0.0001). Patients in the late POCUS group (> 120 min) had a trend to receive more CT scans. The disease distribution, sensitivity, specificity, PPV, and NPV were similar in patients receiving early or late PoCUS for target diagnoses. After adjusting for the confounders, early PoCUS (OR, 2.77, 95% CIs, 1.93–3.98) had a positive impact on shorter LOS. In addition, the effect of early PoCUS became more prominent (OR, 4.91, 95% CIs, 3.39–7.13) on LOS in less than 3 h. Conclusions Early integration of PoCUS is significantly related to shorter LOS in patients with acute flank pain without increasing morbidity and mortality. Our results suggested “PoCUS early” in these patients to possibly alleviate emergency department crowding. Trial registration NCT04149041 at the ClinicalTrial.gov.